Investigation of russian organosilicon stationary phases for gas-liquid chromatography - G. N. Turkeltaub; E. A. Chernyshev (Тонкие химические технологии, 2008)
The thermal stability of organosilicon stationary phases for gas-liquid chromatography has been tested under conditions approximating the real operation of chromatographic column.